2016
DOI: 10.7554/elife.15593
|View full text |Cite
|
Sign up to set email alerts
|

Muscle contraction is required to maintain the pool of muscle progenitors via YAP and NOTCH during fetal myogenesis

Abstract: The importance of mechanical activity in the regulation of muscle progenitors during chick development has not been investigated. We show that immobilization decreases NOTCH activity and mimics a NOTCH loss-of-function phenotype, a reduction in the number of muscle progenitors and increased differentiation. Ligand-induced NOTCH activation prevents the reduction of muscle progenitors and the increase of differentiation upon immobilization. Inhibition of NOTCH ligand activity in muscle fibers suffices to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 78 publications
5
80
0
Order By: Relevance
“…In mouse studies, muscle progenitor cells expressing ERBB3 or NGFR are responsive to paracrine signals secreted by neural crest or neuronal cells 46,47 . During hPSC directed differentiation, SMPCs may be supported by a local micro-environment that includes three dimensional cellular structures and neuronal cells 48 .As several biological processes associated with neuronal cells and transmission of neural impulses were identified by RNA-SEQ in hPSC-SMPC cultures, we expect that neuronal cells are important for hPSC myogenesis throughout directed differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse studies, muscle progenitor cells expressing ERBB3 or NGFR are responsive to paracrine signals secreted by neural crest or neuronal cells 46,47 . During hPSC directed differentiation, SMPCs may be supported by a local micro-environment that includes three dimensional cellular structures and neuronal cells 48 .As several biological processes associated with neuronal cells and transmission of neural impulses were identified by RNA-SEQ in hPSC-SMPC cultures, we expect that neuronal cells are important for hPSC myogenesis throughout directed differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it could act in a mechanism influencing the differentiation of these cell types. Although not explored here, previous studies suggest a role for Yap in ciliogenesis and in the regulation of Notch, a known determinant of cell fate decisions in the airway epithelium (de Lima et al, 2016;Grampa et al, 2016;Kim et al, 2015;Mahoney et al, 2014;Totaro et al, 2017;Tschaharganeh et al, 2013;Tu et al, 2018;Yimlamai et al, 2014).…”
Section: Dynamic Patterns Of Yap Subcellular Localization During Distmentioning
confidence: 93%
“…We also confirmed that MyHC-emb is not expressed by myogenic progenitors or myoblasts and is only expressed by myofibers, implying that the observed effect on differentiation has to be non-cell autonomous, where signals from the myofibers lacking MyHCemb lead to rapid rate of differentiation of the myogenic progenitors, depleting the myogenic progenitor pool. Interestingly, a recent study reported that the Pax7+ muscle stem cell pool and its differentiation is regulated by signals from the differentiated myofibers, including mechanical forces of muscle contraction (Esteves de Lima, et al, 2016).…”
Section: Myhc-embryonic Is a Key Regulator Of Embryonic And Fetal Mymentioning
confidence: 99%